Characterizing HIV-1 genetic subtypes and drug resistance mutations among children, adolescents and pregnant women in Sierra Leone - Yendewa, George A. (2021)
Human immunodeficiency virus (HIV) drug resistance (HIVDR) is widespread in sub-Saharan Africa. Children and pregnant women are particularly vulnerable, and laboratory testing capacity remains limited. We, therefore, used a cross-sectional design and convenience sampling to characterize HIV subtypes and resistance-associated mutations (RAMs) in these groups in Sierra Leone. In total, 96 children (age 2–9 years, 100% ART-experienced), 47 adolescents (age 10–18 years, 100% ART-experienced), and 54 pregnant women (>18 years, 72% ART-experienced) were enrolled. Median treatment durations were 36, 84, and 3 months, respectively, while the sequencing success rates were 45%, 70%, and 59%, respectively, among children, adolescents, and pregnant women. Overall, the predominant HIV-1 subtype was CRF02_AG (87.9%, 95/108), with minority variants constituting 12%. Among children and adolescents, the most common RAMs were M184V (76.6%, n = 49/64), K103N (45.3%, n = 29/64), Y181C/V/I (28.1%, n = 18/64), T215F/Y (25.0%, n = 16/64), and V108I (18.8%, n = 12/64). Among pregnant women, the most frequent RAMs were K103N (20.6%, n = 7/34), M184V (11.8%, n = 4/34), Y181C/V/I (5.9%, n = 2/34), P225H (8.8%, n = 3/34), and K219N/E/Q/R (5.9%, n = 2/34). Protease and integrase inhibitor-RAMs were relatively few or absent. Based on the genotype susceptibility score distributions, 73%, 88%, and 14% of children, adolescents, and pregnant women, respectively, were not susceptible to all three drug components of the WHO preferred first-line regimens per 2018 guidelines. These findings suggest that routine HIVDR surveillance and access to better ART choices may improve treatment outcomes in Sierra Leone.